ANALISIS KARAKTERISTIK MAHASISWA PPG DALAM MEMIMPIN KELOMPOK PADA MATAKULIAH TEKNOLOGI BARU DALAM PENGAJARAN DAN PEMBELAJARAN - Karim, Abdul; Heru, Heru; Japar, Muhammad; Herdiati, Dian (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
This study aims to analyze the leadership characteristics of Teacher Professional Education (PPG) students in the context of the New Technology in Teaching and Learning course. This study uses a qualitative descriptive approach, with research subjects being pre-service PPG students of the Mathematics Education study program. Data collection techniques were carried out through observation and questionnaires to evaluate three main indicators that influence leadership effectiveness, namely: social competence, communication skills, and psychological characteristics. The results of the study showed that communication skills were the most dominant aspect with the highest score, while the other two indicators showed performance that was still at an intermediate level. In addition, mastery of technology plays an important role in supporting the effectiveness of group leadership in the collaborative process. Based on these findings, it is recommended to develop a more comprehensive technology-based leadership training program, in order to improve students' ability to lead groups, especially in technology-based teaching in the digital era.